De eigennaam en het “Zelflofdicht” in de Afrikaanse orale literatuur - Kabuta, Ngo Semzara (Afrika Focus, 2001)
There is a particular poetic genre in African oral literature, based on selfpraise. Selfpraise poetry is built on proper names and formulas, with the metaphor and hyperbole as central style figures. In this article, we situate the proper name inside African culture and show the link between the proper name and selfpraise. Furthermore, we try to grasp the meaning of praising oneself in African culture. The study relies essentially on Cilubà and Kilubà data, but references are made to other languages, in order to show that the genre is not limited to the Lubà oral literature. The first part concentrates on name giving and its meaning. The second part is an analysis of selfpraise poetry, with examples in different languages. Key Words: clan name, hyperbole, inner name, metaphor, oral literature, poetic name, proper name, praise name, selfpraise, social name.